Bank ownership and efficiency in China: what lies ahead in the world's largest nation? - Allen N. Berger; Iftekhar Hasan; Mingming Zhou (Bank of Finland, 2007)
China is reforming its banking system, partially privatizing and permitting minority foreign ownership of three of the dominant 'big four' state-owned banks. This paper seeks to help predict the effects of this change by analysing the efficiency of virtually all Chinese banks in the years 1994-2003. Our findings suggest the big four banks are by far the least efficient and foreign banks the most efficient while minority foreign ownership is associated with significantly improved efficiency. We present corroborating robustness checks and offer several credible mechanisms through which minority foreign owners can increase Chinese bank efficiency. These findings suggest that minority foreign ownership of the big four is likely to significantly improve performance.
URN:NBN:fi:bof-20140807147
Keywords: G21; G28; G34; F23; 330; China; foreign banks; efficiency; foreign ownership